Perceptual training in ice hockey: Bridging the eyes-puck gap using virtual reality - Bloechle, J.-L.; Audiffren, J.; Sauthier, Q.; Mertenat, Q.; Waeber, Y.; Aebischer, D.; Bresciani, J.-P. (Sports Medicine - Open, 2025)
Background Some cognitive and perceptual determinants of sports performance can be arduous to train using conventional methods. In ice-hockey, this is the case for the players` ability to identify the largest exposed area (LEA), i.e., the goal area that is the least covered by the goaltender from a puck perspective. We developed a virtual reality (VR) application to quantify and train the players` ability to identify the LEA from a wide range of shooting positions. Thirty-four professional ice-hockey players were tested. Between two test sessions, half of the players followed a specific feedback-based training (feedback group), whereas the other players practiced without feedback (control group).